2017
DOI: 10.1016/j.carbon.2017.05.087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen and oxygen doped carbon nanotubes on flammability of epoxy nanocomposites

Abstract: To overcome the flammability of epoxy resins, novel nitrogen (CN x ) and oxygen (CO x ) doped CNT were synthesized via CVD method and epoxy nanocomposites at 2 wt.%. constant loading were prepared by three roll milling and cured. The structures of the nanotubes were confirmed by XRD, XPS, SEM and Raman and it was found a very high aspect ratio especially for CO x . Thermal degradation as well as glass transition temperatures and elastic moduli were measured by TGA, DSC and DMTA. The flammability of epoxy nanoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Several studies have also reported the decline in thermal stability through incorporating MWCNTs. They argued that it happens because thermal conductivity increases within the nanocomposite 41 and MWCNTs act as a catalyst. 42 MWCNTs as a catalyst could be explained based on DSC results suggesting that in the case of adding different MWCNTs to the epoxy resin, the completion of the curing reaction is quickened.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have also reported the decline in thermal stability through incorporating MWCNTs. They argued that it happens because thermal conductivity increases within the nanocomposite 41 and MWCNTs act as a catalyst. 42 MWCNTs as a catalyst could be explained based on DSC results suggesting that in the case of adding different MWCNTs to the epoxy resin, the completion of the curing reaction is quickened.…”
Section: Resultsmentioning
confidence: 99%
“…Defects in nanotubes are any alteration of the graphitic lattice, including exohedral, endohedral, and in-plane doping; they are common in the CNTs synthetized by the present method 38 and have been well characterized elsewhere. [39][40][41]52 An atomistic difference between MWNTs and COxs is difficult to appreciate by SEM and TEM, since, as discussed by Botello-Méndez et al, 39 Shabestari et al, 40 and González et al, 52 the meaning of oxygen doping is the formation of different atomic alterations in the graphene layers as carbon-oxygen bonds (eg, by the use of X-ray photoelectron spectroscopy) 52 present the percentage of carbon atoms in graphitic or aliphatic bonds or as part of functional groups such as alcohol, lactones, and carboxyl. This functional group makes COx slightly more reactive than nondoped or MWCNTs.…”
Section: Properties Of Cntsmentioning
confidence: 99%
“…Functionalization is another process where the as-grown CNTs are subjected to a series of chemical processes. 38 In previous biological reports, oxygen-doped MWCNTs (COxs) 39,40 have been used due to the presence of carbonyl, hydroxyl, and oxygenated functional groups enhancing their chemical reactivity, in addition to their higher water solubility 25 Prior to considering MWCNTs as biological scaffolding for grown MSCs in future cardiac protocols, in this study, we aim to evaluate the possible adverse effects on cells and cardiac tissues, using two kinds of CNTs, such as acid functionalized MWCNTs (fMWCNTs) and functionalized oxygen-doped multiwalled CNTs (fCOxs). The objective is to study the effect of fMWCNTs and fCOxs at different concentrations in two biological models with the following purposes: first, on rat MSCs focusing on their growth, proliferation, cell cycle, and possible cell transformation processes to cancer cell and, second, using an in vivo chicken model to study the cardioembryotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 In solving these problems, environmentally friendly ame retardants have become a topic of considerable research interest at present. [10][11][12] Currently, several halogen-free ame retardants, such as graphene, [13][14][15] layered double hydroxide (LDH), 16,17 boron nitride (BN), 18,19 MoS 2 , 20 and carbon nanotubes, 12,21 have been rapidly developed. A small amount of nanoller added into the polymer matrix can result in excellent ame retardancy while simultaneously maintaining or enhancing the other properties of the composites.…”
Section: Introductionmentioning
confidence: 99%